Spatial analysis of sedimentation hazard in the catchment area of the Indonesia nuclear power plant - Alhakim, Euis Etty; Setiawan, Muhammad Anggri; Mellawati, June; Iswanto, Eko Rudi; Setiaji, Abimanyu Bondan Wicaksono (Journal of Degraded and Mining Lands Management, 2025)
Erosion and sedimentation resulting from land use changes can negatively impact watershed quality and threaten sustainability. Watershed quality is particularly crucial in areas designated for energy sector development, such as Nuclear Power Plants (NPPs). One potential NPP site in Indonesia is located downstream of the Raya watershed, where high river sedimentation may affect its performance. This study aimed to determine the spatial pattern of mean annual sediment yield in the Raya watershed using hydrological models. Due to the limited availability of data, secondary data analysis was employed, utilizing a geospatial hydrological modeling approach with the Soil and Water Assessment Tool (SWAT). The Hydrological Response Unit (HRU) was used as an analytical unit to identify physio-geographic similarities based on land use, soil type, and slope, which serve as dynamic hydrological controls. The results reveal the hydrological characteristics of the Raya watershed: an elongated shape, a dendritic river network, and moderate drainage density. The average slope is 12.6%, with a clay-loam soil texture and land cover dominated by dryland forests, oil palm plantations, and mining activities. The SWAT model produced an average sediment yield of 251.7 t/ha/year over a 10-year simulation period, classified as high sedimentation. High to very high sedimentation was predominantly found in the upstream areas, moderate sedimentation at the foothills, and low sedimentation in the alluvial plains downstream. These findings indicate a decline in land quality in the Raya watershed, highlighting the need for conservation measures to ensure the sustainability of the watershed ecosystem.